Decreased IL-10+ regulatory B cells (Bregs) in lupus nephritis patients. (3rd July 2016) - Heinemann, K; Wilde, B; Hoerning, A; Tebbe, B; Kribben, A; Witzke, O; Dolff, S
Abstract : Objectives : Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by B cell-dependent autoantibody production. Recently, a new B-cell subset was discovered that has a regulatory capacity. The aim of this study was to analyse regulatory B cells (Bregs) in SLE patients. Method : Peripheral mononuclear blood cells (PBMCs) of 34 SLE patients fulfilling the American College of Rheumatology (ACR) criteria for SLE and 21 healthy controls (HC) were included. PBMCs were stained for CD19, CD24, and CD38 and analysed by flow cytometry. In vitro stimulated PBMCs with CpG and restimulated with phorbol 12-myristate 13-acetate (PMA) and ionomycin were investigated for IL-10 + Bregs . Results : The percentages of circulating CD19 + CD24 hi CD38 hi cells in HC were not different those in from SLE patients. The percentages of IL-10 + Bregs were significantly decreased in SLE patients, in particular those with lupus nephritis (LN), compared to HC. The proportion was independent of disease activity. Conclusions : This is the first study to demonstrate a decrease in IL-10-producing B cells in LN patients compared to HC, reflecting an impaired regulatory function.